Continuous Non‐Cell Autonomous Reprogramming to Generate Retinal Ganglion Cells for Glaucomatous Neuropathy. (21st May 2015) - Parameswaran, Sowmya; Dravid, Shashank Manohar; Teotia, Pooja; Krishnamoorthy, Raghu R.; Qiu, Fang; Toris, Carol; Morrison, John; Ahmad, Iqbal
Abstract: Glaucoma, where the retinal ganglion cells (RGCs) carrying the visual signals from the retina to the visual centers in the brain are progressively lost, is the most common cause of irreversible blindness. The management approaches, whether surgical, pharmacological, or neuroprotective do not reverse the degenerative changes. The stem cell approach to replace dead RGCs is a viable option but currently faces several barriers, such as the lack of a renewable, safe, and ethical source of RGCs that are functional and could establish contacts with bona fide targets. To address these barriers, we have derived RGCs from the easily accessible adult limbal cells, reprogrammed to pluripotency by a non‐nucleic acid approach, thus circumventing the risk of insertional mutagenesis. The generation of RGCs from the induced pluripotent stem (iPS) cells, also accomplished non‐cell autonomously, recapitulated the developmental mechanism, ensuring the predictability and stability of the acquired phenotype, comparable to that of native RGCs at biochemical, molecular, and functional levels. More importantly, the induced RGCs expressed axonal guidance molecules and demonstrated the potential to establish contacts with specific targets. Furthermore, when transplanted in the rat model of ocular hypertension, these cells incorporated into the host RGC layer and expressed RGC‐specific markers. Transplantation of these cells in immune‐deficient mice did not produce tumors. Together, our results posit retinal progenitors generated from non‐nucleic acid‐derived iPS cells as a safe and robust source of RGCs for replacing dead RGCs in glaucoma. Stem Cells 2013;33:1743–1758